ANALISIS PERBANDINGAN PRODUKTIVITAS PEKERJAAN FONDASI DANGKAL DENGAN MATERIAL BLOK BETON DAN PRODUKTIVITAS PEKERJAAN SESUAI SNI 2836:2008 - Hari Nuryanto; Setya Winarno (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2021)
The use of concrete block material instead of rubble stone on shallow foundation work has many advantages. One aspect that needs to be studied is its workforce productivity. This paper aims to elaborate workforce productivity on shallow foundation work with concrete block material and compare its result to Standard of SNI 2836:2008. Data are collected from construction project which has site-wide construction in Krandon and site-narrow construction in Keringan. The method of data collection has been done by direct investigation from the beginning to the end of the foundation project and complemented by photo and video. These findings have shown that workforce productivity on shallow foundation work with concrete block material both in wide-site and narrow site construction is higher than that of SNI Standards, i.e. 48,87% and 7,14% higher, respectively. Moreover, the productivity rate tends to increase due to the learning effect and adaptation on this foundation work done repetitively. There is a learning curve: y=0,1271.ln(x)+0,4818, in which y=productivity rate and x=work session.